Hydrologic Modeling Analysis from Land Use Scenario Changes in Quebrada Seca and Bermudez Watershed - Chaves Herrera, Matías Adrián (2014)
During the last few years, the expansion of urban cover in the Quebrada Seca-Bermudez watershed has caused a series of floods that have damaged houses, bridges, and other important infrastructure of the area. Hence local governments need a more precise description of these extreme rainfall events through reliable data and modeling watershed, based on 3 different storm durations and five different scenarios: three scenarios from previous years (2001, 2008, and 2012) and 2 forecasted scenarios for the year 2020 (one according to the projected urban growth and the other one based on local urban regulations). Land cover variations were determined using Lansat 7ETM+ images. Both supervised and unsupervised classifications were applied to the satellite images and 6 common classes were obtained: forest, crops, pasture, urban, bare soil and industrial. The Curve Number was assigned based on this information and the soil data with a 1:20 000 scale resolution. A digital elevation model (DEM) with a 30 meters resolution was used to calculate the watershed parameters. Rainfall data over a period of almost 15 years from three meteorological stations were analyzed in order to obtain 2-, 5-, 10-and 25-year return periods. Discharge for all the scenarios was calculated with HEC-HMS program in order to evaluate the changes of urban growth. The results showed a rate of impervious cover of 27% for scenario 1 and 55% for scenario 2. The flow discharge increase for the year2020 is expected to bebetween1% to 14.9% for scenario1.